2016
DOI: 10.1111/cfs.12313
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing the ‘big things’ and the ‘little things’ in child protection cases

Abstract: In this article, we explore how ‘family’ is conceptualized and negotiated in a Mexican and a Chilean child protection institution. We draw on empirical material from two qualitative studies, employing a multi‐method approach. By using a theoretical framework from family sociology, we explore how ‘family’ is done and displayed by families of children in residential care despite socio‐economic, structural and institutional constraints. These displays consist mainly of ‘little things’ of a mundane character, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 36 publications
1
17
0
2
Order By: Relevance
“…Norwegian Child Welfare Services (CWS) are identified as moving from a ‘family service system’ towards a ‘child focused’ system (Gilbert et al ., 2011) and in Chile and Mexico, child protection services – traditionally characterised by a child protection approach – have recently adopted practices that are more family service orientated and focus on family dysfunction and therapeutic orientations (Ursin et al ., 2016). For Cabiati (2015), however, only families with complex needs come to the attention of the services in Mexico, and out-of-home placements are often the only measure used to safeguard children.…”
Section: Contexts and Child Protection Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Norwegian Child Welfare Services (CWS) are identified as moving from a ‘family service system’ towards a ‘child focused’ system (Gilbert et al ., 2011) and in Chile and Mexico, child protection services – traditionally characterised by a child protection approach – have recently adopted practices that are more family service orientated and focus on family dysfunction and therapeutic orientations (Ursin et al ., 2016). For Cabiati (2015), however, only families with complex needs come to the attention of the services in Mexico, and out-of-home placements are often the only measure used to safeguard children.…”
Section: Contexts and Child Protection Systemsmentioning
confidence: 99%
“…This research shows that child protection systems and interactions with families vary across contexts. However, with a few exceptions (Quiroga and Hamilton-Giachritsis, 2014; Ursin et al ., 2016), cross-national comparisons between European countries and other parts of the world, including Latin America, are rare.…”
mentioning
confidence: 99%
“…As a relational context, placement in secure care can be seen as extreme because of its fundamental (if temporary) intervention in all other relational contexts (Enell & Wilińska, 2021.). During such placement, family contacts are greatly limited due to contact restrictions, and these often happen only at a (sometimes considerable) physical distance, while at the same time the family is faced with professionally-created distinctions between "proper" and "improper" family displays (Ursin, Oltedal, & Muñoz, 2017). Ursin et al (2017) found that professionals considered attendance in therapy and parental programs, improved economy, and a nuclear family structure to be "proper" displays, while in contrast, family members valued "little things" like being physically reunited and socializing.…”
Section: The Context Of Secure Care In Swedenmentioning
confidence: 99%
“…During such placement, family contacts are greatly limited due to contact restrictions, and these often happen only at a (sometimes considerable) physical distance, while at the same time the family is faced with professionally-created distinctions between "proper" and "improper" family displays (Ursin, Oltedal, & Muñoz, 2017). Ursin et al (2017) found that professionals considered attendance in therapy and parental programs, improved economy, and a nuclear family structure to be "proper" displays, while in contrast, family members valued "little things" like being physically reunited and socializing. For this reason, secure care challenges family life and family members by creating a unique moral context in which social imaginaries and ideals of family and family lives are revisited.…”
Section: The Context Of Secure Care In Swedenmentioning
confidence: 99%
“…Resulta relevante señalar que gran parte de los estudios utilizan a la Convención y su enfoque de la niñez como marco teórico para analizar los sistemas de protección (Dávila & Naya, 2012;Martínez-Franzoni, 2014;Mieles & Acosta, 2012; Oficina Internacional de los Derechos del Niño, s. f.; Unicef, 2016). Así mismo, una de las consistencias encontradas en la revisión de los diversos estudios es la utilización de metodologías cualitativas para recoger y analizar sus datos (Dávila & Naya, 2012;Martínez-Franzoni, 2014; O#cina Internacional de los Derechos del Niño, s. f.; Olivares & Reyes, 2016;Parada, 2011;Parada et al, 2007;Urzin et al, 2017;Visión Mundial, 2014). Se constató también que gran parte de los estudios o reportes realizados, particularmente en el caso de Honduras, son llevados a cabo por organismos gubernamentales y no gubernamentales; lo anterior implica muchas veces una ausencia de enfoques teóricos que permitan la acumulación del conocimiento relacionado con la niñez y sus sistemas de protección, y el abordaje de sus problemáticas desde una perspectiva afín a las discusiones actuales desde las ciencias sociales.…”
Section: Información Autoresunclassified